Expression Signature of the AT-Rich Interactive Domain Gene Family Identified in Digestive Cancer - Lu, Yongqu; Liu, Zhenzhen; Wang, Wendong; Chen, Xin; Zhou, Xin; Fu, Wei (Frontiers in Medicine, 2022)
Background: The AT-rich interactive domain (ARID) gene family of 15 proteins has an important role in development and proliferation. Gene expression alterations of the ARID family are correlated with the pathogenesis of digestive cancer, but systematic research has not been conducted. Methods: We obtained transcriptome sequencing data, clinical characteristics and stemness indices of the 7 main types of digestive cancer (cholangiocarcinoma, colon adenocarcinoma, oesophageal carcinoma, liver hepatocellular carcinoma, pancreatic adenocarcinoma, rectum adenocarcinoma and stomach adenocarcinoma) from public pan-cancer data to combine the analysis of the expression and prognostic signature of the ARID gene family. The stromal and immune scores for each sample were calculated to explore the correlations between the ARID gene family members and the tumour microenvironment. Results: After screening, 1920 digestive cancer samples were included in our study. ARID3C was expressed at low levels throughout the digestive cancer samples. The expression levels of ARID1A and JARID1C were relatively high, but there was striking heterogeneity across the different cancer types for specific family members. The survival analysis indicated that many genes were significantly related to the prognosis of patients with liver hepatocellular carcinoma. The stemness indices, stromal score, and immune score analysis showed that the expression of a single ARID gene had characteristic consistency in each tumour, but the levels among the different genes still varied. Conclusion: Our systematic study of the ARID gene family and its association with the immune infiltrate, tumour microenvironment and outcomes of digestive cancer patients focus on the complex relations and indicate the need to study each ARID member as an individual in a specific cancer type.